Prensa escrita, regulación y concentración de poder - Garrido Lecca Palacios, Mijael Hernán (2013)
It is usually understood that free competition gives rise to certain groups to prevail over others and obtain the monopoly of some goods and products. However, regarding the press, written or not: Is free competition a masked enemy for the reader, or is it it’s best friend? Should the State prevent an eventual concentration in the power of some media or economic group? In this article, the author argues that considering the market control by an economic groupis a fallacy. On the contrary, he considers that the monopoly on the press doesn’t affect the freedom of the readers.